IMPLEMENTASI POJK NO 11 TAHUN 2020 TERKAIT RENEGOSIASI KONTRAK PADA MASA PANDEMI COVI-19 (STUDI KASUS BANK PERKREDITAS KOTA PAYAKUMBUH) - Dini Rahmatul Husni; Anggun Lestari Suryamizon (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2023)
The spread of the Covid-19 virus is a situation where contracts are very difficult to implement, but can still be implemented by renegotiating. Renegotiation is a process carried out to review or re-discuss contracts that were made and agreed upon prior to the Covid-19 pandemic as a repetition of the negotiation process carried out by the parties. From a legal point of view, renegotiation has a very important role to protect the public interest, namely the interests of both parties so that defaults do not occur which lead to disputes over contracts that have been made and previously agreed upon between customers. Debtors) and Banks (Creditors). BPR X Payakumbuh City is one of the banks that has also implemented Financial Services Authority Regulation (POJK) Number 11 of 2020 concerning Driving the National Economy as a Countercyclical Policy on the Impact of the Spread of the Covid-19 Virus based on Standard Operating Procedures (SOP). The purposes of this study were (1) to find out the implementation of POJK no 11 of 2020 regarding contract renegotiation during the Covid-19 pandemic at BPR X (2) to find out what obstacles occurred in the implementation of POJK no 11 of 2020 concerning Contract Renegotiation During the Covid-19 Pandemic at BPR X. Based on the research results it can be seen that it can be concluded that BPR X Payakumbuh City has implemented POJK No 11 of 2020 concerning Contract Renegotiation during the Covid-1 Pandemic 9 . However, in its implementation there are several obstacles encountered. In addition, an explanation regarding the implementation of POJK No. 11 of 2020 has not been optimal due to Large-Scale Social Restrictions (PSBB) which has made it difficult for BPR X Payakumbuh City and Debtors to hold meetings and discuss existing contract agreements. The implementation implemented by BPR X Payakumbuh City according to the POJK Standard Operating Procedure (SOP) No. 11 of 2020 is quite good.